The significance of the left atrial volume index in prediction of atrial fibrillation recurrence after electrical cardioversion - Toufan, Mehrnoush (J Cardiovasc Thorac Res, 2017)
Introduction: Electrical cardioversion (ECV) is a safe method for the treatment of atrial fibrillation. It seems that left atrial volume index (LAVI) could be a good marker in predicting the success of ECV. The purpose of this study is to assess of the significance of LAVI measurement before ECV in predicting the recurrence of the AF. Methods: Fifty-one patients with AF, selected for ECV were studied in the cardiology department of Tabriz University of medical sciences. The clinical and demographic data of all the patients were obtained. Echocardiography was performed before and also three months after ECV. Patients were separated into two groups: those who maintained SR and those with relapse of AF diagnosed by clinical manifestations and electrocardiography (ECG). Results: Sinus rhythm (SR) was maintained in 76.5 percent of the patients following the three months after ECV. The age, sex and the body mass index (BMI) were not significantly different between SR and AF groups. Two groups showed no significant differences considering pre-ECV medical history including medications and systemic diseases. The initial LAVI of SR group was 42.21±12.4 mL/m(2) and AF group was 96.08±52.21 mL/m(2), the initial LAVI was significantly different between two groups (P = 0.000). The LAVI of SR group decreased significantly (5.69±0.74 mL/m(2)) after three months, LAVI decreased from 42.21 ± 12.4 ml/m(2) to 37.51 ± 10.52 mL/m(2). (P = 0.000). The cut-off point of LAVI value in predicting the maintenance of SR was 55 mL/m(2). Conclusion: The present study indicates that LAVI is a powerful forecaster of the recurrence of AF after ECV. The LAVI measurement could be a useful method in the selection of the patients with AF for ECV.